Current and innovative technologies for pruning harvesting: A review. (December 2017) - Pari, L.; Suardi, A.; Santangelo, E.; García-Galindo, D.; Scarfone, A.; Alfano, V.
Abstract: Pruning residues can provide a significant amount of biomass despite being rarely used as a renewable sources to replace fossil fuels. Exploiting such residues entails creating a sustainable and cost-effective supply chain in which the harvesting and initial processing of the residues play a crucial role. The study is a detailed and accurate survey of the harvesting technologies available in Europe for harvest pruning. After defining the main harvest technologies and the distribution of manufacturers in Europe, the survey details the main groups of implements: shredders, chippers and balers. For each group, the most important configurations are discussed, together with the main characteristics of the machine. Some of the main innovations are detailed (modular machines, non-stop balers, densification of the biomass) which can improve the quality of the product and the economic sustainability of the chain. Highlights: The main balers, shredders and chippers devoted to pruning collection were reviewed. Eighteen type of harvesting systems were classified and described. Among the seventy-five models of implements identified, chippers resulted predominant. The review discussed the main technical efforts required to further optimize the collection.